In situ calibration of passive sampling methods for urban micropollutants using targeted multiresidue GC and LC screening systems. (January 2023) - Allinson, M.; Cassidy, M.; Kadokami, K.; Besley, C.H.
Abstract: In this study, Chemcatcher TM (CC) and Polar Organic Chemical Integrative Samplers (POCIS) passive samplers were chosen to investigate trace organic chemical residues in urban streams of the megacity of Sydney, Australia. In situ calibration with these passive samplers investigated 1392 organic chemicals. Six sets of CC passive samplers fitted with SDB-XC or SDB-RPS disks and six POCIS containing Oasis HLB sorbent were deployed at three sites. Every week for six weeks across three deployments, composite water samples were retrieved from autosamplers, along with one set of CC/POCIS passive samplers. Samples were analysed by Automated Identification and Quantification System (AIQS) GC/MS or LC/QTOF-MS database methods with 254 chemicals detected. The most frequently detected compounds under GC/MS analysis were aliphatic, pesticides, phenols, PAHs, sterols and fatty acid methyl esters while from LC/QTOF-MS analysis these were pesticides, pharmaceuticals, and personal care products. Sampling rates (Rs ) ranged between <0.001 - 0.132 L day −1 (CC SDB-XC, 18 chemicals), <0.001 - 0.291 L day −1 (CC SDB-RPS, 28 chemicals), and <0.001 - 0.576 L day −1 (POCIS Oasis HLB, 30 chemicals). Assessment of deployment duration indicated that about half of the chemicals that were continuously detected across all deployment weeks had maximal simple linear regression R 2 values at four weeks for CC SDB-RPS (seven of 13 chemicals) and at three weeks for POCIS Oasis HLB (seven of 14 chemicals). Where ranges of Rs recorded from the estuarine site were able to be compared to ranges of Rs from one or both freshwater sites, only tributyl phosphate had a higher range of Rs out of 21 possible chemical comparisons, and suggested salinity was an unlikely influence on Rs . Whereas relatively higher rainfall of the third round of deployment aligned with higher Rs across the estuarine and freshwater sites for CC SDB-RPS and POCIS for nearly all possible comparisons. Graphical abstract: Image 1 Highlights: Field comparison of Chemcatcher SDB-XC, SDB-RPS and POCIS Oasis HLB in urban waters. Organic chemicals detected from assessment through multiresidue screening system databases. LC-QTOF-MS analysis of SDB-RPS and POCIS Oasis HLB yielded a similar set of organic chemicals. In situ calibration of 64 chemicals enabled by companion periodic spot water sample collection.